Cross-national Coopetition, Trust, and National Culture Differences:A Case Study of Taiwan-Japan Strategic Alliances in Technology Industry - Chu, Chia-ying (2016)
For decades, entering strategic alliances has become a popular path to gain benefits among international corporations. Whilst high termination rates of cross-national cooperation haunt a number of companies which have an ambition to expand their business through international alliances, between Taiwan and Japan their collaborations tend to show superior performance than other alliances. This paper aims to investigate the successful factors of Taiwan-Japan alliances through conducting survey on Taiwanese senior managers who were involved in the cooperation. We gain access to Taiwanese senior managers who engaged in selected cooperation with Japanese firms by conducting email survey. The rationale of international strategic alliances and specific background of Taiwan and Japan relation will be explored. The results of our study shows the key to a successful alliance is mutual trust and mutual benefits. We conclude that the mutual understanding of each other’s national culture, which resulted from their long historical relations, plays and important role in dealing with difficulties in alliances operation, and lead to a more smooth process and a higher survival rate.